Aplicação e viabilidade de micro-organisos potencialmente probióticos em embutido cárneo fermentado - Carvalho, Catharina Calochi Pires de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Fermented sausages are defined as a mixture of lean meat and fat, the curing salts, sugar, and spices, stuffed into a casing and hung for fermentation and an drying process. The application of probiotic microorganisms shows promise for this type of product, provided that the sausage does not need to be applied to heat treatments during processing, so there not a affecting the viability of microorganisms added. However there is a challenge, due to the sensibility of microorganisms to the curing salts used in this type of product, competition with microorganisms present in meat, resistance to passage through the gastrointestinal tract, besides to interfering sensory characteristics of fermented sausages. Initially were performed resistance tests with the bacteria Enterococcus faecium and Lactobacillus helveticus the front curing salts, sodium chloride, acidity, bile salts and antibiotics. The bacteria showed good viability in the presence of curing salts, but in the presence of sodium chloride only E. faecium showed resistance in three concentrations tested. The microorganisms were not affected in the presence of bile salts remaining in high concentrations, but showed sensibility of different concentrations of pH. In the analysis of resistance to antibiotics, E. faecium showed sensibility to most tested, while the L. helveticus showed resistance. After these analyses, were processed fermented sausages in accordance with the formulations, Formulation 1 (E. faecium), Formulation 2 (L. helveticus) and Formulation 3 (E. faecium + L. helveticus). During the ripening until the end of processing were performed physical and chemical and microbiological analysis, where the results were within the in agreement with legislation. The Formulations 1 and 2 were maintained viable at the end of processing with 8.2 log CFU / g of L. helveticus and 8.4 log CFU / g for E. faecium. After the verification the viability of the bacteria was performed microscopy, ...

Os embutidos fermentados, são definidos como mistura de carne magra e gordura, sais de cura, açúcares, especiarias, embutidos em envoltórios e submetidos à fermentação e secagem. A aplicação de micro-organismos probióticos mostra-se promissora para este tipo de produto, pois não sofrem tratamento térmico durante o processamento, assim não afetando a viabilidade dos micro-organismos adicionados. Entretanto existe o desafio, em virtude da sensibilidade dos micro-organismos aos sais utilizados nesse produto, competição com os micro-organismos presentes na carne, resistência à passagem pelo trato gastrointestinal, além de interferir nas características sensoriais dos embutidos fermentados. Diante disso, foram realizados testes de resistência com as bactérias Enterococcus faecium e Lactobacillus helveticus frente aos sais de cura, cloreto de sódio, acidez, sais biliares e antibióticos. As bactérias apresentaram boa viabilidade na presença de sais de cura, porém na presença de cloreto de sódio apenas E. faecium apresentou resistência nas 3 concentrações testadas. Os micro-organismos não foram afetados na presença dos sais biliares, permanecendo em concentrações elevadas, porém apresentaram sensibilidade em diferentes concentrações de pH. Na análise de resistência a antibióticos, E. faecium apresentou sensibilidade a maioria dos testados, enquanto que o L. helveticus apresentou resistência. Após estas análises, foram realizados os processamentos dos embutidos de acordo com as formulações, Formulação 1 (E. faecium), Formulação 2 (L. helveticus) e formulação 3 (E. faecium + L. helveticus). Durante o período de maturação até final do processamento foram realizados o monitoramento físico-químico e microbiológico do embutido, onde os mesmos ficaram dentro dos padrões estabelecidos pela legislação. As formulações 1 e 2 mantiveram-se a viabilidade no final do processamento com 8,2 log UFC/g ...
Keywords: Tecnologia de alimentos; Alimentos - Microbiologia; Probióticos; Embutidos; Alimentos - Avaliação sensorial; Food technology